PENGARUH RELATIONAL BENEFITS DAN BRAND EXPERIENCES TERHADAP REPURCHASE INTENTION , WILLINGNESS TO PAY MORE DAN WORD OF MOUTH PADA RESTORAN NAMAAZ DINING - Sulisto, Cynthia; Wardhana, Ali (Universitas Multimedia Nusantara, 2024)
Abstract - This research aims to analyze the influence of the Relational Benefits and Brand Experience variables on Repurchase Intentions, Willingness to Pay More, and Word of Mouth at Namaaz Dining Restaurants. The Relational Benefits variable has three dimensions: Confidence Benefits, Social Benefits, and Special Treatment Benefits. Meanwhile, the Brand Experience variable has four dimensions: Sensory Experience, Affective Experience, Behavioral Experience, and Intellectual Experience. Data was obtained by distributing online questionnaires (Google Form) to 168 respondents who had visited Namaaz Dining Restaurant. The data was then processed using the Structural Equation Modeling (SEM) method with SmartPLS software. The research results show that the Relational Benefits and Brand Experience variables positively and significantly influence Repurchase Intentions, Willingness to Pay More, and Word of Mouth. The dimensions of the two independent variables provide different contributions to the dependent variable. These findings provide important managerial implications for Namaaz Dining Restaurant management in designing effective marketing strategies to increase customer loyalty through Relational Benefits and experience of the Namaaz Dining brand. Keywords: Brand Experience; Relational Benefits; Repurchase Intentions; Willingness to Pay; Word of Mouth